Potential of Sambung Nyawa Leaves (Gynura procumbens) as Antidiabetic Mellitus - Mustofa (HM Publisher, 2020)
Diabetes mellitus is a metabolic disease characterized by an increase in blood sugar due to defects in insulin secretion, insulin sensitivity, or both. The number of people with diabetes mellitus in Indonesia has increased every year. The number of people with diabetes is 6.9% in 2013 to 10.9% in 2018. Various therapies have been carried out for the treatment of Diabetes Mellitus, one of which is herbal therapy. Gynura procumbens is a plant that is widely used as a treatment for diabetes mellitus, kidney, rash and fever, and hypertension. The flavonoid content in Gynura procumbens replaces the decrease in blood sugar. This review article attempts to explain the role of Gynura procumbens as an antidiabetic therapy in previous studies. The method used in this article is through searching articles through the NCBI database and Google Scholar. The results of an article search found that Gynura Procumben has antidiabetic potential which can reduce blood sugar in patients with Diabetes Mellitus.